MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF DAN HASIL BELAJAR SISWA MELALUI MODEL PEMBELAJARAN GENERATIF PADA MATERI LARUTAN PENYANGGA - Ahmad Murjani; Abdul Hamid (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2016)
Abstract. Has done research on the use of generative learning model in the material buffer solution which aims to determine (1) the activities of teachers, (2) the activity of students, (3) an increase in the ability to think creatively (4) improvement of learning outcomes, and (5) student response. The study design was a classroom action research (PTK) with two cycles consist of planning, action, observation and evaluation, as well as analysis and reflection. The subjects were students of class XI MS-7 SMA Negeri 2 Banjarmasin by the number of students 33 people. Data collection techniques using observation, testing creative thinking ability and achievement test. Data were analyzed using descriptive quantitative analysis techniques passage and qualitative analysis. The results showed that (1) the activities of teachers has increased by 14.58%, (2) the activity of students has increased by 16.11%, (3) the ability of creative thinking of students for each indicator: (a) fluency increased by 8 33%, (b) flexibility increased by 16.67%, (c) elaboration increased by 8.33%, (d) Originality increased by 1.15%, (4) the results of studying the realm of knowledge of students increased by 15.39%, the result of studying the realm of attitudes increased by 7.40%, the result of studying the realm of skills increased by 8.64%, (5) students gave positive responses.Keyword: creative thinking ability, learning outcomes, buffers, generative learning model